Wet britches and muddy boots : a history of travel in Victorian America - White, John H., 1933- (Railroads past and present., 2013)
What was travel like in the 1880s? Was it easy to get from place to place? Were the rides comfortable? How long did journeys take? Wet Britches and Muddy Boots describes all forms of public transport from canal boats to oceangoing vessels, passenger trains to the overland stage. Trips over long distances often involved several modes of transportation and many days, even weeks. Baggage and sometimes even children were lost en route. Travelers might start out with a walk down to the river to meet a boat for the journey to a town where they caught a stagecoach for the rail junction to catch the train for a ride to the city. John H. White Jr. discusses not only the means of travel but also the people who made the system run-riverboat pilots, locomotive engineers, stewards, stagecoach drivers, seamen. He provides a fascinating glimpse into a time when travel within the United States was a true adventure.